PELATIHAN PEMBUATAN PERANGKAT AJAR SILABUS DAN RPP SMK PGRI 1 LIMAU - Rachmi Marsheilla Aguss; Dina Amelia; zaenal abidin; Permata Permata (Universitas Teknokrat Indonesia, 2021)
Planning can provide guidelines for the implementation of learning, so that it is right on target and effective. One of the goals of educational planning that is very meaningful made by teachers as educational directors is the Syllabus and Learning Implementation Plans and Plans (RPP). Teachers of SMA/Vocational High School (SMK) PGRI 1 Limau are the right target for community service activities considering that the school has not had sufficient technical training. The purpose of this dedication activity is to train and motivate teachers to be able to develop the perfect syllabus and lesson plans. The lesson plan (RPP) is a more specialized planning tool than the syllabus. This educational implementation plan is designed to guide teachers in teaching so that they are not far from educational goals. Recognizing the importance of planning this lesson, teachers should not teach without planning. There is also feedback that shows that the training is suitable with the needs of increasing teacher professionalism and is optimistic that the training can be achieved. Supporting energy for training in the form of space or supporting facilities is sufficient so that the training can run easily, well, on time, and fun. Participants are very supportive of further training. Keywords: Building teacher professionalism with syllabus training, lesson plans, 2013 curriculum.